WITHOUT BORDERS: AN EXEGESIS OF HUMAN RIGHTS OF IMMIGRANT EMPLOYEES IN THE UNITED KINGDOM AND KINGDOM OF SAUDI ARABIA - Nnawulezi, Uche (Journal of Law and Border Protection, 2024)
The principal aim of this paper is to test how States implement international human rights law (IHRL) with respect to the security and welfare of immigrant employees in their country of residence. The paper explicates relevant IHRL shortcomings and contrasts them with rules applicable in situations of human rights abused of immigrant employees. This paper resolves three core questions that are specifically important to immigrant employees as follows: (1) who are considered immigrant employees under each law? Addressing this question permits the testing of whether States understands the status of immigrant employees under International Human Rights Treaty Laws, (2) How is the legal status of immigrant employees managed? (3) Are immigrant employees provided with adequate safeguard along with corresponding security in their place of residence? The outcome of this inquiry revealed that States seldomly apply IHRL understanding of the status of immigrant employees in discussing some of the notable short-comings that contributes to the challenges faced by immigrant employees in their place of residence. Driven fundamentally by efforts to eradicate harmful practices and human rights abuses on immigrant employees, yet immigrant employees are exposed to all manner of employment-related abuses and discrimination in their respective work place. Nonetheless, the paper analyzed cases of discriminatory practices against immigrant employees in UK along with Saudi Arabia. The paper explores what explicit legal and regulatory constraints impedes immigrant rights at his workplace. Moreover, it considers proper measures for managing and overcoming such impediments. The paper adopts analytical approach in its argument through a review of literatures, treaties and conventions. The paper concludes that the right of immigrant employees is universal, inalienable, indivisible and interdependent, regardless of where they are and of their status.